The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1986
DOI: 10.1080/09553008614551081
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Heat-induced Cell Killing as Determined in Three Mammalian Cell Lines Do Not Correspond with the Extent of Heat Radiosensitization

Abstract: Three different cell lines, Ehrlich ascites tumour (EAT) cells, HeLa S3 cells and LM mouse fibroblasts, were used to investigate whether or not the extent of heat killing (44 degrees C) and heat radio-sensitization (44 degrees C before 0-6 Gy X-irradiation) are related. Although HeLa cells were the most heat-resistant cell line and showed the least heat radiosensitization, we found that the most heat-sensitive EAT cells (D0, EAT = 8.0 min; D0, LM = 10.0 min; D0, HeLa = 12.5 min) showed less radiosensitization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1987
1987
2004
2004

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…Neither reducing DNA polymerase b through gene knockout techniques in the mouse cells 11 nor the increase in DNA polymerase b expression by gene transfection 12 resulted in differences in subsequent levels of thermal radiosensitization. These results support the earlier observation of a lack of a correlation between thermal inhibition of polymerase b and radiosensitization 9,10 . However, these data do not refute the observation that thermal radiosensitization occurs at least in part through inhibition of the repair of radiation damage assayed by cell and DNA strand break recovery 1-3 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Neither reducing DNA polymerase b through gene knockout techniques in the mouse cells 11 nor the increase in DNA polymerase b expression by gene transfection 12 resulted in differences in subsequent levels of thermal radiosensitization. These results support the earlier observation of a lack of a correlation between thermal inhibition of polymerase b and radiosensitization 9,10 . However, these data do not refute the observation that thermal radiosensitization occurs at least in part through inhibition of the repair of radiation damage assayed by cell and DNA strand break recovery 1-3 .…”
Section: Discussionsupporting
confidence: 90%
“…In addition, it was also shown that there was a correlation between thermal inactivation of DNA polymerase b, the DNA repair enzyme reputed to be involved in base excision repair 4 , and thermal radiosensitization in a wide range of mammalian cells [5][6][7][8] . Even though extensive correlation was reported, some studies showed a lack of such a correlation, and thus the relationship between thermal inactivation of DNA polymerase b and thermal radiosensitization was not unequivocal 9,10 . Recent molecular biology techniques have permitted the testing of this relationship more directly with the use of cells that have had DNA polymerase b knocked out 11 and cells that have been transfected with the DNA polymerase b gene to give elevated expression 12 .…”
Section: Introductionmentioning
confidence: 95%